Feasibility Study of Fiber Optic Infrastructure Development Plan in Indonesia - Lessy Sutiyono Aji (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Demands for high-speed and reliable internet service significantly increase. Optical fiber, as a transmission media, has better performance and speed when compared to wireless media. However, optical fiber network development is challenging on the last mile mainly due to higher investment costs than wireless networks. This paper presents the feasibility study of the fiber optic network development plan in Indonesia. The analysis showed that the optical fiber network development was not feasible in many regions if it relied only on private sectors. In this regard, the government should facilitate the development of optical fiber networks so that telecommunication operators can develop a network in previously unreachable areas